2014
DOI: 10.5779/hypothesis.v12i1.229
|View full text |Cite
|
Sign up to set email alerts
|

Philanthrocapitalism, past and present: The Rockefeller Foundation, the Gates Foundation, and the setting(s) of the international/global health agenda

Abstract: In recent years the Bill and Melinda Gates Foundation has emerged as this era's most renowned, and arguably its most influential, global health player. A century ago, the Rockefeller Foundation-likewise founded by the richest, most ruthless and innovative capitalist of his day-was an even more powerful international health actor. This article reflects critically on the roots, exigencies, and reach of global health philanthropy, comparing the goals, paradigms, principles, modus operandi, and agenda-setting role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
123
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 164 publications
(131 citation statements)
references
References 109 publications
2
123
0
6
Order By: Relevance
“…Since then, these entities have shrewdly drawn on the WHO for legitimacy, while maintaining a stranglehold over its decision-making capacity; many are controlled by actors who cannot be regarded as appropriate or ethical global health authorities and who have no public accountability (Adams and Martens, 2015;Birn, 2014;Nambiar et al, 2013;Richter, 2012). The Soviet Union, facing its own political and economic crises, no longer provided a counterbalance to this 'Washington Consensus'.…”
Section: From the Cold War To The Rise Of Neoliberalism: The Beginninmentioning
confidence: 99%
“…Since then, these entities have shrewdly drawn on the WHO for legitimacy, while maintaining a stranglehold over its decision-making capacity; many are controlled by actors who cannot be regarded as appropriate or ethical global health authorities and who have no public accountability (Adams and Martens, 2015;Birn, 2014;Nambiar et al, 2013;Richter, 2012). The Soviet Union, facing its own political and economic crises, no longer provided a counterbalance to this 'Washington Consensus'.…”
Section: From the Cold War To The Rise Of Neoliberalism: The Beginninmentioning
confidence: 99%
“…This fragmentation, many argue, results from the increased agenda-setting power of private foundations, notably the Bill and Melinda Gates Foundation, which has undermined the ability of publicly mandated institutions like the World Health Organization and recipient governments to promote integrated health policies, threatening democratic global health governance (Cueto 2004; Brown et al 2006; McCoy and McGoey 2011; Birn 2014). Moreover, ethnographic studies have demonstrated that private foundations’ success in shaping health policy in line with their convictions has often been achieved by limiting their focus to ‘safe issues’ and marginalizing other perspectives, as in the case of malaria (Eckl 2014), or by appropriating broader policy agendas, as in the case of GAVI’s health system strengthening investment (Storeng 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Leadership and authority for health at the global scale that were conventionally a responsibility of international organisations specialising in health (ie, WHO) have been challenged by the ascent of non-state actors and GHI in the global health governance system 5051 Although private philanthropy has historically played a role in international health agenda setting, scholars have expressed concerns about the influence of foundations and private industry actors in the global health governance system in the 21st century, including their relationships with governments, public–private partnerships and international organisations 52–54…”
Section: Discussionmentioning
confidence: 99%